Peningkatan Umur Simpan Produk Ayam Kremes - Tjahja Muhandri; Mega Sefrina (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Ayam kremes is one of specialty foods of Semarang City. Product of ayam kremes "A" located in Semarang is difficult to transport to a distant place due to short shelf life. It begins to emerge an odor after 10 hours. The objectives of this study were to determine the factors causing the problem and to improve the shelf life of the product. To solve the problem, a framework base on PDCA cycle was used. The activity was conducted in fives stages: identification of the real process in industry, analysis of the causing factors using Ishikawa diagram, improvement of production procedure, production trial using the new procedure, and organoleptic analysis. The results showed that the causes of the problem were unclean washing process, cross-contamination during carcass stabbing and unstandardized frying process. The new proposed procedures were improvement on washing process, removal of the carcass stabbing process, addition of soaking treatment to the chicken carcasses in a mixture of salt and lemon juice after a chicken carcass washed, and standarization of the frying process. The proposed procedure was able to extend the shelf life of ayam kremes "A" up to 72 hours.